Acid‐Resistant Coatings on Marble. Issue 10 (22nd June 2016) - Naidu, Sonia; Blair, Jeremy; Scherer, George W.
Abstract : Inorganic coatings are being developed to protect marble monuments and sculpture from weathering. In this work, the acid resistance of hydroxyapatite (HAP), calcium oxalate, and calcium tartrate coatings on Carrara marble were compared. To quantify the rate of attack on calcite, the pH of the solution was measured. This approach was validated by confirming that the rate of dissolution of untreated calcite inferred from the change in pH agrees with data in the literature. Calcium tartrate coatings were incomplete, and the mineral is so soluble that it offered no significant protection. Calcium oxalate forms coherent coatings, so it serves as a sacrificial coating in spite of having solubility comparable to that of calcite. HAP was deposited from aqueous solutions of 1 M diammonium hydrogen phosphate (DAP), with or without millimolar additions of CaCl2 (which improved coverage) and (NH4 )2 CO3 (which resulted in cracking). The best HAP coatings remained porous; nevertheless, they were comparable to oxalate coatings in the short term and superior in the long term, reducing the dissolution rate by about 40%.